2021
DOI: 10.34024/pensata.2021.v10.12620
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalismo, precariedade e diversidade: notas sobre a circulação de pesquisadores indianos na universidade britânica

Abstract: A partir de uma pesquisa sobre as circulações de pesquisadores indianos em ciências sociais na Europa, analiso as articulações entre neoliberalismo e precariedade acadêmica na universidade britânica a partir de um ponto de vista pós-colonial. Para tanto, o artigo está estruturado do seguinte modo: (i) introduzo e situo sociológica e historicamente o objeto deste estudo; (ii) realizo uma discussão conceitual que coloca em perspectiva quatro questões-chave deste estudo: neoliberalismo, precariedade, mobilidade e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…One could argue that many people would prefer short-term contracts over permanent employment for either professional or personal reasons. Although not impossible, that is not what recent research has shown (Ferreira, 2021). Ethnographic scholarship states that, in general, the period following PhD training is marked by an aspiration to settle and create long-lasting institutional and personal bonds.…”
Section: The Global Survey: Findings Gaps and Overturesmentioning
confidence: 96%
See 1 more Smart Citation
“…One could argue that many people would prefer short-term contracts over permanent employment for either professional or personal reasons. Although not impossible, that is not what recent research has shown (Ferreira, 2021). Ethnographic scholarship states that, in general, the period following PhD training is marked by an aspiration to settle and create long-lasting institutional and personal bonds.…”
Section: The Global Survey: Findings Gaps and Overturesmentioning
confidence: 96%
“…To say that anthropology has a colonial history is nowadays quite a commonsensical idea, but it might cause some controversial reaction to state that contemporary anthropology continues to rely on neo-colonial, or imperial (Ribeiro, 2011) structures of power/knowledge. As we have argued elsewhere (Ferreira 2017(Ferreira , 2021, such articulation has been undertaken under the cover of the contemporary lexicon of globalization, transnationality and, more recently, decoloniality. In other words, neoliberal science and higher education re-appropriate colonial and postcolonial histories of intellectual circulations between colonial and metropolitan regions -and the imaginaries that make people move (Hall, 1997) -by re-signifying them through a globalizational semantics that euphemize precisely those postcolonial legacies.…”
Section: Precarity and Epistemological Inequalitiesmentioning
confidence: 99%